Profile of Physical Conditions of High School Futsal Players in Gorontalo - Ramadan, Gilang; Samin, Giofandi (Universitas Muhammadiyah Kuningan, 2023)
The purpose of this study was to determine the physical condition of each futsal player at SMA Negeri 1 Gorontalo; this was to provide an overview to the coach regarding the physical condition of each individual. This research method uses a descriptive method to reveal facts in the field; the sample of this study consisted of 33 futsal players at SMA Negeri 1 Gorontalo. The results of this study are from 33 futsal players who have been tested and measured. All players fall into the category of lacking in VO2Max conditions, strength, speed and reaction speed. This study concludes that the tests and measurements gave the coach a basic picture of the player's physical condition. Hence, the coach needs to be careful in choosing and sorting out training programs to improve the physical condition of futsal players.